X-RAY MICROBEAM AS ONE OF THE MOST MODERN ARTICULATORY METHODS OF INVESTIGATION - Titiaieva, Y. (Linguistic and Conceptual Worldviews, 2019)
The article substantiates the necessity of phonetic, in particular articulation, researches. The role of articulatory research in the study of the nature of sound units and their significance for linguistics and practical use are determined. The preconditions for studying the sound system of the language with the help of experimental techniques are specified. The history of occurrence and development of experi- mental phonetic researches in Ukraine and in the world is analyzed. The main methods of articulation research, including types of X-ray examination as one of the most important articulatory techniques, are considered. There are brought to the light the history and procedure of film-roentgenography with its implementation in Ukrainian linguistics. A number of tasks performed by experimental phonetics, as well as the possibility of applying its results in diﬀerent fields of knowledge are outlined. The article is focused on X-ray microbeam – one of the most contemporary types of X-ray re- search, which was created by the Japanese scientist Osama Fujimura in the second half of the last century. The history of creating the device for such studies is traced, the procedure of collecting articu- lation information (preparation for recording, the placement of tracking beads, type of the articulated material and tasks set forth) is described. The main advantages of X-ray microbeam in comparison with other methods are determined: it gives information about all the sounds of human speech, does not distort the pronunciation, causes minimal harm to health, allows studying large masses of information quickly and automatically. At the and, the conclusion about the feasibility of usage X-ray microbeam in experimental phonet- ics is made. It is confired the significance of such a method, which lies in the interdisciplinary type of research, the generation of new knowledge in the field of phonetics and the addition of existing infor- mation with the help of the latest technologies.